Rare missense variants in the PPP2R5D gene associated with Parkinson's disease in the Han Chinese population. (17th April 2022) - Ning, Pingping; Li, Kelu; Ren, Hui; Yang, Hongju; Xu, Yanming; Yang, Xinglong
Highlights: This study identified two PPP2R5D exonic variants [p.R91S and p.R523L] in Chinese patients with sporadic PD. The two variants appears to be novel and affect a highly conserved residue in the PPP2R5D protein. Burden analysis showed that PD patients had abundant rare variants in PPP2R5D . Abstract: Background: Recent studies have reported an association between PPP2R5D mutations and early-onset levodopa-responsive parkinsonism, but this gene has yet to be analyzed comprehensively in a large Parkinson's disease (PD) cohort. Objective: The aim of this study was to examine the frequency and spectrum of PPP2R5D mutations in a Han Chinese cohort with early- or late-onset PD. Methods: The 5′- and 3′-untranslated regions as well as coding sequence of the PPP2R5D gene were sequenced in 668 patients with sporadic PD. Novel variants were detected and validated based on genomic databases, as well as verified using genetic data from unrelated controls. Sanger sequencing was used to confirm rare mutations found by next-generation sequencing. Results: Two of the 145 EOPD patients carried two novel, unique PPP2R5D exonic variants (p.R91S, p.R523L), while none was detected in late-onset Parkinson's disease (LOPD). Two variants were predicted to be "disease-causing" by Mutation Taster, and both mutations were found to be highly conserved across species. Conclusion: Our study identified two rare PPP2R5D variants among Han Chinese EOPD patients, which broadens the spectrum of PPP2R5D mutations potentially associated with the disease.